Prenatal Acetaminophen Exposure and its Associated Risk for Attention Deficit Hyperactivity Disorder - Noah J. Spillers; Norris C. Talbot; Patrick M. Luther; Gianni H. Ly; Caylin J. Roberts; Shahab Ahmadzadeh; Sahar Shekoohi; Omar Viswanath; Alan D. Kaye (Health Psychology Research)
Acetaminophen is one of the most commonly used over-the-counter antipyretic and analgesic drugs on the market and has been relevant in the medical world for almost a hundred years. It has maintained an excellent reputation as a safe therapeutic in several types of patient profiles. However, the number of children diagnosed with neurodevelopmental disorders, namely ADHD, have been on the rise. Recent findings have indicated an association between in utero exposure to acetaminophen and an increased risk of developing neurodevelopmental disorders such as ADHD in offspring. The mechanism by which this potential side effect occurs is difficult to pinpoint. However, it is known that the metabolism of acetaminophen is known to cause oxidative stress, which has been shown to influence the developing fetus. This review highlights the epidemiological data indicating the correlation between prenatal acetaminophen exposure and ADHD and discusses several proposed theories by which this phenomenon may occur. While there is not yet enough clinical evidence to prove that acetaminophen may cause ADHD, there is a strong enough correlation to indicate a warning to pregnant patients of the potential risks. The risks and benefits of treatment should be considered so that the patient may continue with the course of action with the most favorable outcome. This review was mainly based on manuscripts pulled from Google Scholar and PubMed. The purpose of this literature review is to assist clinicians to better understand lesser-known risks in acetaminophen usage in pregnant patients.